2023
DOI: 10.1038/s41467-023-38429-1
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin alternates between A and B compartments at kilobase scale for subgenic organization

Hannah L. Harris,
Huiya Gu,
Moshe Olshansky
et al.

Abstract: Nuclear compartments are prominent features of 3D chromatin organization, but sequencing depth limitations have impeded investigation at ultra fine-scale. CTCF loops are generally studied at a finer scale, but the impact of looping on proximal interactions remains enigmatic. Here, we critically examine nuclear compartments and CTCF loop-proximal interactions using a combination of in situ Hi-C at unparalleled depth, algorithm development, and biophysical modeling. Producing a large Hi-C map with 33 billion con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 83 publications
3
25
0
Order By: Relevance
“…Specifically, more B-type compartments transitioned into A-type compartments, coinciding with the enrichment of activated epigenetic marks such as H3K4me3 and H3K27ac, and the loss of inhibitory epigenetic marks like H3K27me3. These observations are consistent across various cellular processes, [98][99][100][101] highlighting the strong connections between epigenetic modifications and chromatin states, and their pivotal role in transcriptional regulation during trastuzumab adaptation.…”
Section: Discussionsupporting
confidence: 75%
“…Specifically, more B-type compartments transitioned into A-type compartments, coinciding with the enrichment of activated epigenetic marks such as H3K4me3 and H3K27ac, and the loss of inhibitory epigenetic marks like H3K27me3. These observations are consistent across various cellular processes, [98][99][100][101] highlighting the strong connections between epigenetic modifications and chromatin states, and their pivotal role in transcriptional regulation during trastuzumab adaptation.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, punctate loops in mammals are typically enriched for CTCF and RAD21, a member of the cohesin complex [7,[33][34][35][36]. We also recently showed that CTCF loops are often comprised of fairly diffuse interactions when viewed at high resolution [5] (Figure 2A, left panel).…”
Section: Hicrayon Improves the Visualization Of Protein Occupancy Ove...mentioning
confidence: 71%
“…Using this high-resolution Hi-C map in lymphoblastoid cell lines (LCLs) [5], we colored contacts by HiCrayon to visualize the overlap between chromatin interactions and published ChIP-seq for CTCF (red) and RAD21 (blue). We found that HiCrayon at high resolution can help visualize the center of loop foci where an intense Hi-C signal coincides with CTCF and cohesin together (purple) (Figure 2A).…”
Section: Hicrayon Improves the Visualization Of Protein Occupancy Ove...mentioning
confidence: 99%
See 2 more Smart Citations